The Association between Seasonal Variation in Vitamin D, Postural Sway, and Falls Risk: An Observational Cohort Study - Marie-Louise Bird; Keith D. Hill; Iain Robertson; Madeleine J. Ball; Jane K. Pittaway; Andrew D. Williams (Journal of Aging Research)
Introduction. Low serum vitamin D levels are associated with increased postural sway. Vitamin D varies seasonally. This study investigates whether postural sway varies seasonally and is associated with serum vitamin D and falls. Methods. In a longitudinal observational study, eighty-eight independently mobile community-dwelling older adults (69.7 ± 7.6 years) were evaluated on five occasions over one year, measuring postural sway (force platform), vitamin D levels, fall incidence, and causes and adverse outcomes. Mixed-methods Poisson regression was used to determine associations between measures. Results. Postural sway did not vary over the year. Vitamin D levels varied seasonally (P<0.001), peaking in summer. Incidence of falls (P=0.01) and injurious falls (P=0.02) were lower in spring, with the highest fall rate at the end of autumn. Postural sway was not related to vitamin D (P=0.87) or fall rates, but it was associated with fall injuries (IRR 1.59 (CI 1.14 to 2.24, P=0.007). Conclusions. Postural sway remained stable across the year while vitamin D varied seasonally. Participants with high values for postural sway demonstrated higher rates of injurious falls. This study provides important evidence for clinicians and researchers providing interventions measuring balance outcomes across seasons.